PENGARUH PENGGUNAAN APLIKASI QUIZIZZ PAPER MODE TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV SD INPRES PANAIKANG 11 KOTA MAKASSAR - Febriani, Mawar; AP, Nurfaizah; Faisal, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the use of the Quizizz Paper Mode application on the learning outcomes of Pancasila Education of fourth-grade students of SD Inpres Panaikang 11 Makassar City. The main problem underlying this study is the low learning outcomes of students. This study uses experimental research with a quantitative approach, with a quasi-experimental design (nonequivalent control group design). The population is 41 fourth-grade students of SD Inpres Panaikang 11 Makassar City with a sample of 21 students of class IV A (experimental) and 20 students of class IV B (control) selected by purposive sampling technique. Data were collected through observation sheets and learning outcome tests. The results of descriptive analysis indicate that the implementation of the learning process using the Quizizz[ Paper Mode application is classified as very good. The results of inferential analysis with an independent sample t-test show a p-value of 0.004 <0.05, indicating a significant difference in the average posttest results between the experimental and control classes. Better learning outcomes occurred in the experimental class, supported by a higher average posttest score than the control class. Therefore, it can be concluded that the use of the Quizizz Paper Mode application has a significant impact on the learning outcomes of fourth-grade students in the Pancasila Education Unit (UPT SPF) of Panaikang 11 Elementary School, Makassar City. The use of Quizizz Paper Mode can be an effective strategy for teachers because it positively influences the quality of Pancasila Education learning in elementary schools.